Health Promotion Strategy with MHP (Mask-wearing, Hand-washing and Physical Distancing) - Herlinawati Herlinawati; Mohamad Sadli; Suzana Indragiri; Sri Rizki Indira Dewi (Qualitative and Quantitative Research Center, 2022)
The purpose of this study was to determine the relationship between health promotion strategies and the MHP activities (Mask-wearing, Hand-washing and Physical Distancing). The design in this research is Cross Sectional. The population consists of people of productive age (15-59 years) after the December 2020 period totaling 2,738 people. The number of samples was 96 respondents who were taken by systematic random sampling. Data collection is done by using interviews. The instrument in this study was a questionnaire. The data were statistically analyzed using the Chi Square test at a significance level of 5% (0.05). The results of the statistical test showed that advocacy (p = 0.009), social support (p = 0.023) and community empowerment (p = 0.001) had a significant relationship with the MHP activities in Prajawinangun Wetan Village in 2021. The results of this study can be followed up by conducting counseling and counseling by health workers involving community leaders regarding the MHP activities including using masks, washing hands, maintaining distance regularly and conducting evaluations to ensure the continued application of MHP activities.